Breeding gains and changes in morphotypes of Nordic spring wheat (19011993) under contrasting environments - Ortíz, R.; Lund, B.; Anderson, S.B. (2003)
Phenotypic diversity among 75 Nordic spring wheat cultivars was assessed in a glasshouse experiment, in which plots had no fertilizer or received 14-3-23 NPK plus Mg. On average, the fertilizer application delayed flowering by one day, shortened plant height (PH), as well as enhanced the number of fertile tillers (NFT), fresh and dry straw weight (FSW and DSW, respectively), but influenced negatively the dry matter content in the straw (DMCS) and the number of kernels per spike (K/S). The cultivar-by-fertilizer interaction did not affect significantly days to flowering (DF), PH, FSW, DSW, DMCS, thousand kernel weight, and K/S. Only NFT was significantly affected by this interaction. There were significant differences among cultivars for all characteristics, and the breeding gains were significant for improving earliness (as determined by DF), shortening PH, as well as for reducing DSW and DMCS irrespective of the environment. On average, FSW was low in newer cultivars grown in high inputs, while NFT was low in newer cultivars when grown in low inputs. The country of origin affected significantly DF, PH, DMCS, K/S, and 1000-kernel weight. On average, cultivars developed for Finland and Norway were significantly taller, and had higher DMCS. Finnish cultivars also flowered 1 or 2 days earlier and showed higher K/S than cultivars adopted in southern Scandinavia or Norway.